1994
DOI: 10.1002/j.1460-2075.1994.tb06399.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagen sensitivity and suppression of position-effect variegation result from mutations in mus209, the Drosophila gene encoding PCNA.

Abstract: The mus209B1 mutant of Drosophila melanogaster exhibits a complex pleiotropy of temperature‐sensitive (ts) lethality, hypersensitivity to DNA‐damaging agents such as ionizing radiation and methyl methanesulfonate, suppression of position‐effect variegation (PEV), and female sterility. Our discovery that mus209 encodes proliferating cell nuclear antigen (PCNA), which is an indispensable component of the DNA replication apparatus, suggests that alterations to chromosome replication may underlie that pleiotropy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 70 publications
0
59
0
Order By: Relevance
“…In Drosophila, the PCNA mutant mus209B1 shows suppression of position effect variegation in addition to its hypersensitivity to DNA damage. These results provided strong genetic proof for the role of Drosophila PCNA in transcriptional repression and heterochromatin maintenance (33). Again, the mechanism by which Drosophila PCNA may mediate repression was not established.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Drosophila, the PCNA mutant mus209B1 shows suppression of position effect variegation in addition to its hypersensitivity to DNA damage. These results provided strong genetic proof for the role of Drosophila PCNA in transcriptional repression and heterochromatin maintenance (33). Again, the mechanism by which Drosophila PCNA may mediate repression was not established.…”
Section: Discussionmentioning
confidence: 94%
“…In Saccharomyces cerevisiae, PCNA is involved in gene silencing through CAF-1-dependent and -independent mechanisms (32). In Drosophila, mutation of PCNA suppresses position effect variegation (33), indicating its role in transcriptional repression and heterochromatin function. In mammals, PCNA was shown to interact with histone deacetylase 1(HDAC1), implying a role for histone hypo-acetylation in DNA replication (34).…”
mentioning
confidence: 99%
“…A recent study in Saccharomyces cerevisiae has shown that several mutations in PCNA decrease silencing at telomeres and at the mating-type HMR locus (7). Furthermore, mutations in the Drosophila PCNA gene mus209 suppress repression in the vicinity of heterochromatin (8). The disruption of epigenetic silencing has been attributed to the inability of some of these mutants to associate with CAF-1.…”
mentioning
confidence: 99%
“…Mutations in DNA replication factors lead to defects in position-effect variegation in flies (36)(37)(38) and silencing defects at telomeres and silent mating loci in yeast (39)(40)(41). Likewise, perturbations of cellular acyl pools in yeast by genetic inactivation orthologs of Acaca (42) and Acss1 (43) cause global alterations in histone acetylation and genomewide expression.…”
Section: Discussionmentioning
confidence: 99%